The Reception of the Mantra of Light in Republican Period Chinese Buddhism - An, Saiping (Religions, 2023)
This paper examines the utilization of the mantra of light and its associated maṇḍala practices by Wang Hongyuan 王弘願 (1876–1937), a Chinese Buddhist during the Republican Period, and his adherents, which has not yet been noticed by previous scholars. With the import of esoteric Buddhist doctrines and practices from Japan, the mantra of light, which was a rarely used mantra in pre-modern China, gained renewed significance. This led to the widespread adoption of the ritual practices of this mantra by Wang Hongyuan and his surrounding Buddhist groups in early modern China. The rituals of this mantra were used as a supplement or substitute for near-death Pure Land practices. This paper presents Pure Land Buddhist practices intertwined with esoteric Buddhist elements or “esoteric” approaches to Pure Land rebirth in modern Chinese Buddhism which have been overlooked by previous scholars.